Crystal structure of 4-aminobenzoic acid–4-methylpyridine (1/1) - Kumar, M. Krishna (Acta Crystallogr E Crystallogr Commun, 2015)
In the title 1:1 adduct, C(6)H(7)N·C(7)H(7)NO(2), the carboxylic acid group is twisted at an angle of 4.32 (18)° with respect to the attached benzene ring. In the crystal, the carboxylic acid group is linked to the pyridine ring by an O—H⋯N hydrogen bond, forming a dimer. The dimers are linked by N—H⋯O hydrogen bonds, generating (010) sheets.